2015
DOI: 10.1590/0001-3765201520140041
|View full text |Cite
|
Sign up to set email alerts
|

Chemical compositions and termiticidal activities of the heartwood from Calophyllum inophyllum L.

Abstract: Wood extractives from heartwood of Callophylum inophyllum (bintangor) were obtained by shaker method and analyzed for their constituents by gas chromatography-mass spectrometry (GC-MS). Ten compounds were identified by ethanol (EtOH) solvents, fourteen by methanol (MeOH) and only nine by petroleum ether (PETETHR). Major compounds were contributed by monoterpenes (75.11%, 53.75%) when extracted with EtOH and PETETHR solvents. The anti-termitic assay of the wood extracts was also investigated against Coptotermes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
(12 reference statements)
1
3
0
1
Order By: Relevance
“…Conversely, n-hexane dissolves nonpolar compounds, while ethyl acetate dissolves semipolar components(Lukmandaru, 2012). The methanol extract displayed a dark brown color, ethyl acetate extract exhibited a lighter brown color than did the methanol extract, and n-hexane extract appeared yellow.Furthermore, the yield of the n-hexane extract surpassed that of the ethyl acetate extract, consistent with the results reported byEe et al (2011), who observed a higher production of the n-hexane extract from the bark of C. inophyllum compared with that of the ethyl acetate extract Kadir et al (2015). reported that the yield of the methanol extract from C. inophyllum heartwood was higher than those of other solvents.…”
supporting
confidence: 90%
“…Conversely, n-hexane dissolves nonpolar compounds, while ethyl acetate dissolves semipolar components(Lukmandaru, 2012). The methanol extract displayed a dark brown color, ethyl acetate extract exhibited a lighter brown color than did the methanol extract, and n-hexane extract appeared yellow.Furthermore, the yield of the n-hexane extract surpassed that of the ethyl acetate extract, consistent with the results reported byEe et al (2011), who observed a higher production of the n-hexane extract from the bark of C. inophyllum compared with that of the ethyl acetate extract Kadir et al (2015). reported that the yield of the methanol extract from C. inophyllum heartwood was higher than those of other solvents.…”
supporting
confidence: 90%
“…Analysis. In order to identify certain phytochemical constituents as well as to illustrate the chromatogram fngerprint in the C. inophyllum extract, GC-MS analysis was performed using Agilent Technologies GC-MS 7890A/5975C Series (Agilent, USA) equipped with a capillary column (30 m in length × 0.25 mm in diameter × 0.25 μm flm thickness) (partly modifed from Kadir [21]). Te spectrum database reported in the W08N08 library (John Wiley & Sons, Inc., USA) was used to identify the phytochemical components of the extract.…”
Section: Gas Chromatography-mass Spectrophotometrymentioning
confidence: 99%
“…But at the activation temperature of 800 C, the value of nitrogen content went up by 0.40%. In the process of activation also formed new pores due to the erosion of carbon atoms through oxidation or heating [15].…”
Section: Ultimate Analysis Of Activated Carbon Of Nyamplung Seed Shellmentioning
confidence: 99%